BRAF V600E expression and distribution in desmoplastic infantile astrocytoma/ganglioglioma. Issue 3 (April 2014) - Koelsche, C.; Sahm, F.; Paulus, W.; Mittelbronn, M.; Giangaspero, F.; Antonelli, M.; Meyer, J.; Lasitschka, F.; von, A.; Reuss, D.
<x xml:space="preserve">Abstract</x> Aims Desmoplastic infantile astrocytoma/ganglioglioma (DIA/DIG) is a rare primary neuroepithelial brain tumour typically affecting paediatric patients younger than 24 months. Knowledge about genetic alterations in DIA/DIG is limited. However, a previous study on BRAF V600E mutation in paediatric glioma revealed a BRAF mutation in one of two tested DIAs/DIGs. The limited number of cases in that study did not allow any conclusion about mutation frequency of BRAF in this tumour entity. Methods We collected a series of 18 DIAs/DIGs for testing BRAF V600E mutational status by BRAF V600E immunohistochemistry (clone VE1). Cases with sufficient DNA were tested for BRAF V600E mutation by pyrosequencing. Results Three out of 18 DIAs/DIGs presented with VE1 binding. A considerable proportion of BRAF V600E mutated tumour cells was detected in the cortical tumour component, whereas the pronounced leptomeningeal tumoural stroma was predominantly negative for VE1 binding. Pyrosequencing confirmed BRAF V600E mutation in two of three VE1‐positive cases. Conclusion BRAF V600E mutation affects a subset of DIAs/DIGs and offers new therapeutic opportunities.